Pengaruh Kemudahan Penggunaan, Risiko, Keamanan, dan Fitur Layanan terhadap Minat Masyarakat Menggunakan Aplikasi OVO di Kota Samarinda - Zulfikar Zulfikar; Khofifah Tri Apriliyati (Politeknik Negeri Samarinda, 2022)
AbstractThe Effect of Ease of Use, Risk, Security, and Service Features on Public Interest in Using OVO in Samarinda City. Thesis for the Department of Accounting, Finance and Banking Study Program, under the guidance of Mr. Dr. Sudarlan, SE, MT as the first supervisor and Zulfikar, S.E, M.SA (Humbis) as a second guide. This study uses quantitative methods. Data collection techniques in This study uses the technique of distributing questionnaires, observation, and literature. The sample in this study were 250 respondents. Data analysis techniques to be used used in this research are Validity Test, Reliability Test, Classical Assumption Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Linear Regression Test Multiple, t test, f test, correlation coefficient, coefficient of determination and use IBM SPSS Version 19 software. The results of this study partially variable Ease of Use, Risk, Security, and Service Features Against Public Interest in Using OVO in Samarinda City., seen from Tcount < T table (-0483 < 1.969) and sig value of 0.629 < 0.05, partially the risk variable has a significant positive effect on Community Interest using the OVO application in Samarinda City, seen from Tcount > T table (4.648 > 1.969) and the sig value of 0.000 > 0.05, partially the security variable has no negative effect and not significant to Community Interest in Using OVO in Samarinda City, seen from Tcount < T table (-0.322 < 1.969) and sig value of 0.748 < 0.05, partially service feature variables have no significant negative effect on Community interest in using Ovo applications in the City Samarinda, seen from Tcount > Ttable (2,069 > 1,985) and the sig value of 0.041 > 0.05, simultaneously the convenience variable p use, risk, security and service features on public interest in using the OVO application in Samarinda City as seen from Fcount > Ftable (5,812 > 4,383) and a sig value of 0.000 < 0.05.